Analysis of Factors Influencing Choice of Milk Marketing Channel among Small and Medium Dairy Farmers in Punjab - Brar, Ravneet Singh; Kaur, Inderpreet; Singh, Varinder Pal; Chopra, Shruti (Indian Journal of Dairy Science, 2018)
Dairy sector in Punjab has emerged as most crucial auxiliary for diversification of agriculture. Dairying alone contributes about 85 per cent to the livestock sector in Punjab (2010-11). More than 70 per cent of milk production and marketed milk are contributed by small and medium farmers, which make them an indispensible part of milk production system. Still, majority of small and medium farmers really on traditional or unorganized marketing channels with marginal remuneration. Thus, there is need of gradual morphing of milk marketing channel from unorganized to the organized sector that would provide basis for a more inclusive growth for all categories of dairy farmers and simultaneously ensure disposal of quality raw milk and processed dairy products for the end user. Present study unravels the factors influencing the choice of marketing channel by small and medium sized dairy farmers in Punjab. The results of the binomial logit regression model revealed that age of the household and distance to selling point has negatively influenced the producers’ likelihood towards organized sector. Other factors influencing the choice were found to be total milch animal holding, price of milk sold and availability of advances. Study clearly indicates the need to strengthen collection of milk, promotion of liberal loans, remunerative prices and lesser intermediaries in milk value chain for growth and expansion of dairy business in Punjab.